Poverty in metropolitan cities - Alam, S. Manzoor ed.; Alikhan, Fatima; Andhra Pradesh (India). Planning Department; Hyderabad Urban Development Authority (New Delhi : Concept Pub, 1987)
Papers presented at the National Seminar on "Problems of Low-income Groups in Metropolitan Cities of India", Osmania University, Hyderabad, in March 1983, and organized by the Planning Department, Government of Andhra Pradesh, Hyderabad Urban Development Authority, and the Centre for Area Studies, Osmania University.
Includes bibliographies and index.
Keywords: Urban poor -- India -- Congresses; Slums -- India -- Congresses